Microcirculation-guided resuscitation in sepsis: the next frontier? - Damiani, Elisa; Carsetti, Andrea; Casarotta, Erika; Domizi, Roberta; Scorcella, Claudia; Donati, Abele; Adrario, Erica (Frontiers in Medicine, 2023)
Microcirculatory dysfunction plays a key role in the pathogenesis of tissue dysoxia and organ failure in sepsis. Sublingual videomicroscopy techniques enable the real-time non-invasive assessment of microvascular blood flow. Alterations in sublingual microvascular perfusion were detected during sepsis and are associated with poor outcome. More importantly, sublingual videomicroscopy allowed to explore the effects of commonly applied resuscitative treatments in septic shock, such as fluids, vasopressors and inotropes, and showed that the optimization of macro-hemodynamic parameters may not be accompanied by an improvement in microvascular perfusion. This loss of "hemodynamic coherence", i.e. the concordance between the response of the macrocirculation and the microcirculation, advocates for the integration of microvascular monitoring in the management of septic patients. Nonetheless, important barriers remain for a widespread use of sublingual videomicroscopy in the clinical practice. In this review, we discuss the actual limitations of this technique and future developments that may allow an easier and faster evaluation of the microcirculation at the bedside, and propose a role for sublingual microvascular monitoring in guiding and titrating resuscitative therapies in sepsis.